Market-Based loss mitigation practices for troubled mortgages following the financial crisis - Sumit Agarwal; Gene Amromin; Itzhak Ben-David; Souphala Chomsisengphet; Douglas D. Evanoff (Federal Reserve Bank of Chicago, 2010)
The meltdown in residential real-estate prices that commenced in 2006 resulted in unprecedented mortgage delinquency rates. Until mid-2009, lenders and servicers pursued their own individual loss mitigation practices without being significantly influenced by government intervention. Using a unique dataset that precisely identifies loss mitigation actions, we study these methods - liquidation, repayment plans, loan modification, and refinancing - and analyze their effectiveness. We show that the majority of delinquent mortgages do not enter any loss mitigation program or become a part of foreclosure proceedings within 6 months of becoming distressed. We also find that it takes longer to complete foreclosures over time, potentially due to congestion. We further document large heterogeneity in practices across servicers, which is not accounted for by differences in borrower population. Consistent with the idea that securitization induces agency conflicts, we confirm that the likelihood of modification of securitized loans is up to 70% lower relative to portfolio loans. Finally, we find evidence that affordability (as opposed to strategic default due to negative equity) is the prime reason for redefault following modifications. While modification terms are more favorable for weaker borrowers, greater reductions in mortgage payments and/or interest rates are associated with lower redefault rates. Our regression estimates suggest that a 1 percentage point decline in mortgage interest rate is associated with a nearly 4 percentage point decline in default probability. This finding is consistent with the Home Affordable Modification Program (HAMP) focus on improving mortgage affordability.
Keywords: D1; D8; G1; G2; 330; loan modifications; financial crisis; household finance; mortgages; securitization; Finanzmarktkrise; Hypothek; Refinanzierung; Privater Haushalt; Haushaltsökonomik; Kreditsicherung; USA